Accionar de enfermería en crisis hipertensiva basado en el modelo de Peplau - Lalón Ramos Luz María (2022)
ABSTRACT: Hypertensive crises are a frontline health problem, being the most frequent cause of consultation in the First Level of Care around the world, affecting people in their lifestyle and daily activities. For this reason, an analytical bibliographical study was carried out on nursing actions in hypertensive crisis based on Peplau's model, proposing pharmacological and non-pharmacological interventions. By collecting information from various indexed digital Journals and from graduate universities, Google Scholar, Elsevier, PubMed, Redalyc, Scielo, Europe PMC; disseminated between 2016 and 2022, of which 46 publications were taken for the bibliographic review, first a triangulation was carried out using the criteria of the various authors cited in terms of pathophysiology, clinical manifestations and treatment of hypertensive crises; where, relevant aspects were taken such as: description of the contributions in the management of the pathology and level of effectiveness. Regarding the contributions we can name theorists such as Dorothea Orem, and Virginia Henderson, who served as a guide for the development of nursing activities through an affective relationship, to reach the approach of Peplau's theory of interpersonal relationships, in the This research work is based, where the nursing staff will determine the need for care to potentiate interpersonal therapeutic development in hypertensive crisis patients, making them identify their potential problems and can solve them as part of their daily activities.